Impact of Hashimoto’s thyroiditis on the tumor microenvironment in papillary thyroid cancer: insights from single-cell analysis - Ma, Hongzhe; Li, Guoqi; Huo, Diwei; Su, Yangguang; Jin, Qing; Lu, Yangxu; Sun, Yanyan; Zhang, Denan; Chen, Xiujie (Frontiers in Endocrinology, 2024)
This study investigates the impact of Hashimoto's thyroiditis (HT), an autoimmune disorder, on papillary thyroid cancer (PTC) microenvironment using a dataset of 140,456 cells from 11 patients. By comparing PTC cases with and without HT, we identify HT-specific cell populations (HASC) and their role in creating a TSH-suppressive environment via mTE3, nTE0, and nTE2 thyroid cells. These cells facilitate intricate immune-stromal communication through the MIF-(CD74+CXCR4) axis, emphasizing immune regulation in the TSH context. In the realm of personalized medicine, our HASC-focused analysis within the TCGA-THCA dataset validates the utility of HASC profiling for guiding tailored therapies. Moreover, we introduce a novel, objective method to determine K-means clustering coefficients in copy number variation inference from bulk RNA-seq data, mitigating the arbitrariness in conventional coefficient selection. Collectively, our research presents a detailed single-cell atlas illustrating HT-PTC interactions, deepening our understanding of HT's modulatory effects on PTC microenvironments. It contributes to the understanding of autoimmunity-carcinogenesis dynamics and charts a course for discovering new therapeutic targets in PTC, advancing cancer genomics and immunotherapy research.